ENHANCED EXCITONIC NONLINEAR ABSORPTION IN GAINAS/INP MULTIPLE QUANTUM WELLS. - Fox, A; Maciel, A; Ryan, J; Scott, MD (Optical Soc of America, 1987)
The saturation of the absorption coefficient of both bulk and multiple-quantum-well (MQW) samples of Ga//0//. //4//7In//0//. //5//3As/InP was measured at room temperature. The MQW sample showed strong excitonic enhancement of the 2-D absorption edge at both 4 K and room temperature. The measurements were made using a tunable Co:MgF//2 laser. Q-switched pulses of 1- mu s duration and 30-W peak power were used to generate intensities up to 2 multiplied by 10**5 W cm**-**2 in the sample. The transmission of the samples was measured between 1. 58 and 1. 67 mu m as a function of incident laser intensity, and the intensity dependence of the absorption coefficient was deduced. The absorption coefficient of the MQW sample was obtained as a function of photon energy at four incident laser intensities: (a) 8 W cm**-**2; (b) 30 W cm**-**2; (c) 130 W cm**-**2; (d) 700 W cm**-**2. At the lowest intensity the n equals 1 heavy-hole exciton transition is seen at 774 meV. This transition begins to saturate at very low intensities, and at 30 W cm**-**2 the peak in the absorption spectrum is bleached. The absorption coefficient at 775 meV (1. 60 mu m) is studied as a function of incident laser intensity.